An efficient waste management technique with IoT based smart garbage system. (2023) - Karthik, M.; Sreevidya, L.; Nithya Devi, R.; Thangaraj, M.; Hemalatha, G.; Yamini, R.
Abstract: Many cities now have public trash cans that are overflowing due to the continual growth of rubbish. The dustbins are not cleaned on time by the bin collector. As a result, the city becomes unclean, the environment becomes contaminated, and the atmosphere becomes unsanitary. It distributes a foul odor in the waste, which may be harmful to our human health. To avoid this problem, keep the environment clean and create a healthy environment. The ultrasonic sensor detects the amount of trash in the trash can. We created a low-cost embedded device for city sanitation that allows the web server to track the location of each street. It's simple to tell whether a dustbin is full or not. As soon as the level hits a certain maximum pre-setted limit, automatically the information is sent to the bin collector. The bin collector will use the internet to access their mobile phone and will take immediate action to clean up the city.